Population Roadmap Integration Strategy In Accelerating Regional Development In North Sumatra Province 2025–2029 Towards A Golden Indonesia 2045 - Heri Pranata Satria (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Population development enters a strategic phase towards a Golden Indonesia 2045 through the Population Development Roadmap (PJPK) 2025–2029. North Sumatra Province, which is at the peak of the demographic bonus with the proportion of the productive age population reaching 67.23% and a dependency ratio of 48.75% (2025), has a great opportunity to accelerate regional development. However, the implementation of PJPK integration at the district/city level still faces various obstacles. This study aims to analyze the problem of integrating 30 PJPK indicators into regional planning documents (RPJMD and RKPD) and formulate an effective strategy. Using a qualitative approach with document analysis, SIGA April 2026 secondary data, and PJPK Progress Monitoring as of April 9, 2026, this study identifies three main problems: the lack of optimal internalization of PJPK indicators, weak cross-sector coordination, and low technical capacity and political commitment of regional apparatus. The analysis shows that the root of the problem lies in the system of competency development of apparatus that is not yet population-oriented, the lack of continuous technical assistance from the province, and the planning culture that is still sectoral. Using the Analytic Hierarchy Process (AHP), the structured technical mentoring model was selected as the best alternative with a score of 0.412. The main recommendation is the issuance of a Governor's Regulation on Structured Technical Assistance and the Mandatory Integration of 30 PJPK Indicators into regional planning documents. This policy is expected to strengthen cross-sector synergy, increase the capacity of the apparatus, and ensure that PJPK becomes the main reference for accelerating regional development in North Sumatra towards a Golden Indonesia 2045.